1999
DOI: 10.1109/91.811231
|View full text |Cite
|
Sign up to set email alerts
|

Type-2 fuzzy logic systems

Abstract: We introduce a type-2 fuzzy logic system (FLS), which can handle rule uncertainties. The implementation of this type-2 FLS involves the operations of fuzzification, inference, and output processing. We focus on "output processing," which consists of type reduction and defuzzification. Type-reduction methods are extended versions of type-1 defuzzification methods. Type reduction captures more information about rule uncertainties than does the defuzzified value (a crisp number), however, it is computationally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
604
0
17

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,440 publications
(661 citation statements)
references
References 36 publications
5
604
0
17
Order By: Relevance
“…Mendel also suggest that interval type-2 FLCs are more adaptive as they are able to realize more complex input-output relationships which cannot be achieved by a type-1 FLC [62]. Our results also support this from the IT2 SOFLCs ability to adaptively regulate multi variable anesthesia set points based on adjusting the delivery rates of two different drugs with different pharmacodynamic and pharmacokinetic characteristics.…”
supporting
confidence: 77%
“…Mendel also suggest that interval type-2 FLCs are more adaptive as they are able to realize more complex input-output relationships which cannot be achieved by a type-1 FLC [62]. Our results also support this from the IT2 SOFLCs ability to adaptively regulate multi variable anesthesia set points based on adjusting the delivery rates of two different drugs with different pharmacodynamic and pharmacokinetic characteristics.…”
supporting
confidence: 77%
“…At present, the use of logic systems (FLS) has increased, as can be observed in [24][25][26][27][28][29][30]. The Interval Type 2 fuzzy set has a fuzzy membership function, the membership grade for each element of this set is a fuzzy set in [0, 1], as can be observed in [31][32][33][34][35]. In generalized Type 2 fuzzy sets the uncertainty is represented in volume and is able to handle greater uncertainty in the system.…”
Section: Fuzzy Logic Systemsmentioning
confidence: 99%
“…The main feature of T2FLSs is the Footprint of Uncertainty (FOU) describing the uncertainties and nonlinearities. Many studies have shown that T2FLS are much more robust to cope with uncertainties and nonlinearities compared to T1FLS [15][16][17][18][19][20]. In this paper, T2FLS is applied to a SAPF to control DC bus voltage and to reduce harmonic distortion.…”
Section: Introductionmentioning
confidence: 99%